Epoxy resin adhesive with high bio-based content and intrinsic flame retardance and preparation method thereof

By mixing components A and B with high bio-based content, and combining them with bio-based flame retardants and toughening agents, the intrinsic flame retardancy of epoxy resin adhesives was achieved. This solved the problems of low bio-based content and insufficient flame retardant performance, improved mechanical properties and aging resistance, and expanded application scenarios.

CN121160264APending Publication Date: 2025-12-19YILIAN FUNCTIONAL MATERIALS (SHANGHAI) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511497831.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

Existing bio-based epoxy adhesives have low bio-based content and insufficient flame retardant properties, while traditional petroleum-based epoxy adhesives rely on non-renewable resources and are flammable. Additive flame retardants suffer from migration and performance loss issues.

Method used

The mixture uses a high bio-based content of component A and component B. Component A contains bio-based epoxy resin, reactive diluent and toughening agent, while component B contains bio-based flame retardant and accelerator. Intrinsic flame retardancy is achieved through molecular-level binding, avoiding the defects of additive flame retardants.

Benefits of technology

Achieving stable flame retardant effects with high bio-based content avoids migration and performance loss, improves mechanical properties and aging resistance, expands application scenarios, and reduces dependence on fossil resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an epoxy resin adhesive with high bio-based content and intrinsic flame retardance and a preparation method, and particularly relates to the technical field of epoxy resin adhesives, and the epoxy resin adhesive is prepared by mixing and curing a component A and a component B according to a mass ratio of 100: 30-100: 45. According to the invention, the flame-retardant property and the bio-based property are deeply combined from the molecular level, so that the product has a stable and lasting flame-retardant effect while the high bio-based ratio is ensured, the traditional cognition that the flame-retardant property is necessarily sacrificed for increasing the bio-based content is thoroughly changed, the synergistic problem of high bio-based property and high flame retardance is broken through, the molecular level performance fusion is realized, and the flame-retardant property of the product is improved. The material is endowed with permanent intrinsic flame retardance, the problems of migration and failure of a small-molecule flame retardant are avoided, stable chemical bonding is formed between flame-retardant components and an adhesive matrix by virtue of an intrinsic flame-retardant mechanism, the problems of migration and precipitation of a traditional additive type flame retardant are completely eradicated, and performance failure and environmental hidden dangers caused by falling of the flame retardant are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of epoxy adhesive, more particularly, the present application relates to an epoxy adhesive with high bio-based content and intrinsic flame retardation and a preparation method thereof. BACKGROUND

[0003] At present, most of the so-called bio-based epoxy adhesives on the market only add a small amount of bio-based toughening agent such as cashew nut shell oil or diluent, the bio-based content is usually <30%, and in order to meet the flame retardation requirement, a large amount of inorganic hydroxide or halogen-containing, phosphorus-containing small molecule flame retardant still needs to be added. These additive flame retardants often have problems such as migration, precipitation and deterioration of mechanical properties. Traditional epoxy adhesives mostly rely on bisphenol A type and other petroleum-based raw materials, consume non-renewable resources, and are flammable themselves. Although there are studies on the development of bio-based epoxy adhesives from renewable resources such as vegetable oil and lignin, either the bio-based content is low and it is difficult to achieve true green replacement, or the flame retardation performance decreases significantly after increasing the bio-based proportion, which cannot meet the use requirements in high-risk scenarios. SUMMARY

[0004] In order to overcome the above-mentioned defects of the prior art, the present application provides an epoxy adhesive with high bio-based content and intrinsic flame retardation and a preparation method thereof, so as to solve the problems raised in the background art.

[0005] To achieve the above-mentioned purpose, the present application provides the following technical scheme: an epoxy adhesive with high bio-based content and intrinsic flame retardation, which is formed by mixing and curing A component and B component in a mass ratio of 100:30 to 100:45; The A component is composed of the following components, and the sum of the weight fractions of each component is 100 parts: 60 to 80 parts of bio-based epoxy resin; 5 to 12 parts of bio-based active diluent; 3 to 8 parts of bio-based toughening agent; The B component is composed of the following components, and the sum of the weight fractions of each component is 100 parts: 20 to 35 parts of bio-based curing agent; 5 to 15 parts of bio-based flame retardant; 1 to 5 parts of bio-based accelerator; Among them, the bio-based flame retardant is phytic acid or phytate.

[0006] Preferably, the epoxy value of the bio-based epoxy resin is 0.45 eq / 100g to 0.55 eq / 100g.

[0007] Preferably, the bio-based epoxy resin includes itaconic acid-based epoxy resin and succinic acid-based epoxy resin.

[0008] Preferably, the itaconic acid-based epoxy resin accounts for 40% to 60% of the total weight of the bio-based epoxy resin, and the succinic acid-based epoxy resin accounts for 20% to 40% of the total weight of the bio-based epoxy resin.

[0009] Preferably, the bio-based active diluent is eugenol glycidyl ether.

[0010] Preferably, the bio-based toughening agent is cashew nut shell oil modified elastomer.

[0011] Preferably, the bio-based curing agent is cashew nut shell oil phenolic amine or abietic acid anhydride derivative.

[0012] Preferably, the bio-based accelerator is a lignin-derived phenolic accelerator.

[0013] Also provided is a method for preparing the epoxy resin adhesive as described above, comprising the following steps: (1) preparing component A: mixing and stirring the bio-based epoxy resin, bio-based active diluent and bio-based toughening agent at 50 to 70°C for 30 to 60 minutes; (2) preparing component B: mixing and stirring the bio-based curing agent, bio-based flame retardant and bio-based accelerator at 40 to 60°C for 20 to 40 minutes; (3) mixing component A and component B at a mass ratio of 100:30 to 100:45 when used, and curing at room temperature for 24 hours or at 80 to 120°C for 1 to 3 hours.

[0014] Preferably, the mixing and stirring in step (1) is carried out under vacuum conditions, with a vacuum degree of -0.09MPa to -0.1MPa.

[0015] Technical effects and advantages of the present application: By constructing a full-bio-based component synergistic epoxy adhesive system, compared with the traditional petroleum-based epoxy adhesive which relies on fossil raw materials and has a low bio-based proportion, and some bio-based epoxy adhesives which only increase the content of a single bio-based raw material but cannot achieve effective flame retardation, by precisely designing the bio-based composition of A and B components, the A component uses bio-based epoxy resins such as itaconic acid and succinic acid as the matrix, and is matched with bio-based active diluents and toughening agents, and the B component introduces bio-based characteristic flame retardant curing agents and phytic acid-based bio-based flame retardants, so that the adhesive realizes bio-based from the matrix resin to the functional additives, without relying on traditional added flame retardants, but deeply combining the flame retardation performance with the bio-based attribute from the molecular level, ensuring that the product has stable and persistent flame retardation effect while having high bio-based proportion, completely changing the traditional cognition that increasing bio-based content must sacrifice flame retardation performance, breaking through the synergistic problem of high bio-based and high flame retardation, realizing molecular-level performance fusion, and the bio-based flame retardant is bonded to the polymer network through reactive functional groups, giving the material permanent intrinsic flame retardation, avoiding the migration and failure problems of small molecule flame retardants. Through formula design, the synergistic improvement of flame retardation, mechanics, and aging resistance performance is realized. In order to achieve flame retardation effect, traditional added flame retardant adhesives often need to add a large amount of inorganic flame retardants, which not only destroys the adhesive matrix structure, leading to significant attenuation of mechanical properties such as tensile shear, peeling, etc., but also easily causes long-term use performance failure due to migration and precipitation of flame retardants. The bio-based toughening agent improves the toughness of the matrix, the bio-based active diluent regulates the system compatibility, and the molecular-level interaction between the bio-based intrinsic flame retardant curing agent and the flame retardant avoids the damage of added flame retardants to the matrix. Ultimately, the adhesive still maintains good mechanical strength on the basis of excellent flame retardation performance, and the wet heat aging resistance performance is greatly improved, solving the long-term technical contradiction in the industry that flame retardation enhancement must damage the mechanical performance, expanding the application scenarios of epoxy adhesives, overcoming the performance short board of traditional flame retardant adhesives, and realizing multi-performance synergistic optimization. Through the design of full bio-based components, the dependence on fossil resources is greatly reduced, and the environmental load in the production and use process is reduced. At the same time, relying on the intrinsic flame retardation mechanism, the flame retardation component and the adhesive matrix form a stable chemical bond, completely eliminating the migration and precipitation problems of traditional added flame retardants, avoiding performance failure and environmental hazards caused by the shedding of flame retardants, not only realizing the breakthrough of product performance, but also constructing a full life cycle environmental protection path of epoxy adhesives from preparation, service to waste, providing an innovative technical scheme for the green upgrading of epoxy adhesives. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work are within the protection scope of the present application.

[0017] In the present application, all performance tests follow the following national standards (GB) or international standards (ASTM): Bio-based content: determined according to ASTM D6866-22 Standard Test Methods for Determining Bio-based Content of Solid, Liquid, and Gaseous Samples Using Radiocarbon Analysis.

[0018] Tensile shear strength: determined according to GB / T 7124-2023 Adhesives Determination of Tensile Shear Strength (Rigid to Rigid), test piece is 100 mm x 25 mm x 1.5 mm steel sheet, bonding area is 12.5 mm x 25 mm, tensile speed is 5 mm / min.

[0019] T-peel strength: determined according to GB / T 2791-2020 Adhesives T- Peel Strength Test Method Flexible to Flexible, test piece is 150 mm x 25 mm x 0.5 mm aluminum foil.

[0020] Heat deflection temperature (HDT): determined according to GB / T 1634.2-2019 Plastics Determination of the Heat Distortion Temperature of Plastics and Elastomers Part 2: Plastics and Rigid Rubbers, load is 1.82 MPa, temperature rising rate is 120 ℃ / h.

[0021] Flame retardant grade: determined according to the vertical burning method specified in UL 94-2021 Flammability of Plastic Materials for Parts in Devices and Appliances, sample thickness is 1.6 mm.

[0022] Limiting oxygen index LOI: determined according to GB / T 2406.2-2009 Plastics Determination of the Burning Behavior by Oxygen Index Method Part 2: Room Temperature Test.

[0023] Moisture and heat aging resistance: determined according to GB / T 12000-2017 Plastics Determination of the Effects of Exposure to Wet Heat, Water Spray and Salt Spray, the sample is placed in an environment of 85 ℃ and 85% relative humidity, and after 1000 hours, the mechanical properties are tested, and the strength retention rate is calculated.

[0024] Flame retardant migration: To evaluate the stability of the flame retardant component, an accelerated migration test was used. After the cured sample was placed in a constant temperature oven at 60°C for 168 hours, it was taken out and observed under natural light to see if there were any precipitates on the surface. The surface was gently wiped with a fingertip to check if there was any powder falling off.

[0025] Example 1 The present embodiment provides a high-bio-based content intrinsic flame-retardant epoxy resin adhesive and a preparation method thereof.

[0026] Raw materials and proportions are by weight parts: Component A: Itaconic acid-based epoxy resin 50 parts, epoxy value: 0.50 eq / 100g, bio-based carbon content: 95%; Butanedioic acid-based epoxy resin 30 parts, epoxy value: 0.53 eq / 100g, bio-based carbon content: 98%; Eugenol glycidyl ether 8 parts, bio-based active diluent, epoxy value: 0.40 eq / 100g; Gamma-aminopropyl triethoxysilane KH-550, silane coupling agent 1 part.

[0027] Component B: Cashew phenol-DOPO-amine derivative intrinsic flame-retardant curing agent 35 parts, phosphorus content: 8.5%, nitrogen content: 4.2%, bio-based carbon content: 85%; Gamma-aminopropyl triethoxysilane KH-550: 2 parts; The mixing mass ratio of component A to component B is 100:35.

[0028] Preparation method Preparation of component A: Add all raw materials in component A to a 500 mL three-necked flask equipped with a stirrer, temperature control device and vacuum interface. Heat to 60°C, start stirring at 300 rpm, and control the vacuum degree to -0.095 MPa by starting the vacuum system. Keep the temperature and stirring for 45 minutes, then stop the vacuum and heating, and discharge the material. A uniform and transparent component A is obtained, which is sealed and stored.

[0029] Preparation of component B: Add all raw materials in component B to a 250 mL single-necked flask, and place it in a 60°C water bath. Stir mechanically at 200 rpm for 30 minutes until the system becomes a homogeneous transparent liquid. Component B is obtained and stored in a sealed container.

[0030] Mixing and curing: Before use, A component and B component were weighed in a beaker according to the mass ratio of 100:35, stirred manually with a glass rod for 5 minutes to complete uniformity, the mixed glue liquid was injected into a preheated polytetrafluoroethylene mold, placed in a blast oven at 80°C for 2 hours, then naturally cooled to room temperature, demolded, and the cured sample and sheet were obtained for performance test.

[0031] Performance test results: The cured material was tested for performance, and the results were as follows: Total bio-based content (ASTM D6866): 78%; Tensile shear strength (steel-steel, GB / T 7124): 32 MPa; T-peel strength (aluminum-aluminum, GB / T 2791): 39 N / mm; Heat distortion temperature (1.82 MPa, GB / T 1634.2): 168°C; Flame retardant rating (UL 94, 1.6 mm): V-0 level; Limiting oxygen index (GB / T 2406.2): 32%; Wet heat aging resistance (85°C / 85% RH, strength retention rate after 1000h): 88%.

[0032] Example 2 Raw materials and proportions were calculated by weight parts: A component: Itaconic acid-based epoxy resin: 40 parts, epoxy value: 0.50 eq / 100g, bio-based carbon content: 95%; Butanedioic acid-based epoxy resin: 20 parts, epoxy value: 0.53 eq / 100g, bio-based carbon content: 98%; Eugenol glycidyl ether: 5 parts, bio-based active diluent, epoxy value: 0.40 eq / 100g.

[0033] γ-Aminopropyl triethoxysilane KH-550, silane coupling agent 1 part; B component: Cardanol-DOPO-amine derivative: 30 parts, phosphorus content: 8.5%, nitrogen content: 4.2%, bio-based carbon content: 85%; KH-550: 1 part; The mixing mass ratio of A component to B component was 100:30.

[0034] Preparation method Preparation of A component: Put all raw materials in A component into a 500 mL three-necked flask equipped with a stirrer, temperature control device and vacuum interface, heat to 55℃, start stirring at 300 rpm, and control the vacuum degree at -0.09 MPa by starting the vacuum system, and keep the temperature and stirring for 40 minutes, then stop the vacuum and heating, and discharge to obtain a uniform and transparent A component, which is stored in a sealed state.

[0035] Preparation of B component: Put all raw materials in B component into a 250 mL single-necked flask, and mechanically stir at 200 rpm in a 50℃ water bath for 25 minutes until the system becomes a uniform transparent liquid to obtain B component, which is stored in a sealed state.

[0036] Mixing and curing: Before use, weigh A component and B component in a beaker at a mass ratio of 100:35, manually stir with a glass rod for 5 minutes until completely uniform, pour the mixed glue liquid into a preheated polytetrafluoroethylene mold, and place it in a forced air oven at 100℃ for 1.5 hours, then naturally cool to room temperature, and demold to obtain the cured sample and sheet, which are used for performance testing.

[0037] Performance test results Total bio-based content: 75%; Tensile shear strength: 28 MPa; T-peel strength: 35 N / mm; Heat distortion temperature: 160℃; Flame retardant level: V-0 level; Limiting oxygen index: 30%; Moisture and heat aging resistance (strength retention rate after 1000 hours): 85%.

[0038] Example 3 This example provides a viscous glue of a formula to illustrate the effect of parameter changes within the scope of the claims.

[0039] Raw materials and proportions are by weight parts: A component: Itaconic acid-based epoxy resin: 48 parts, epoxy value: 0.50 eq / 100g, bio-based carbon content: 95%; Butanedioic acid-based epoxy resin: 24 parts, epoxy value: 0.53 eq / 100g, bio-based carbon content: 98%; Eugenol glycidyl ether: 12 parts, bio-based active diluent, epoxy value: 0.40 eq / 100g.

[0040] KH-550: 2 parts B component: Cardanol-DOPO-amine derivative: 45 parts, phosphorus content: 8.5%, nitrogen content: 4.2%, biobased carbon content: 85%; KH-550: 3 parts The mass ratio of the A component to the B component is 100:45 Preparation method Preparation of the A component: All raw materials in the A component are added to a 500 mL three-neck flask equipped with a stirrer, temperature control device, and vacuum interface. The temperature is raised to 65°C, the stirring is started at a speed of 300 rpm, and the vacuum system is started to control the vacuum degree at -0.1 MPa. The system is kept under these conditions for 50 minutes, and then the vacuum and heating are turned off. The product is discharged, and a uniform transparent A component is obtained, which is sealed and stored.

[0041] Preparation of the B component: All raw materials in the B component are added to a 250 mL single-neck flask and placed in a 55°C water bath. The system is mechanically stirred at a speed of 200 rpm for 35 minutes until it becomes a uniform transparent liquid. The B component is obtained and sealed for storage.

[0042] Mixing and curing: Before use, the A component and the B component are weighed in a beaker at a mass ratio of 100:35, manually stirred with a glass rod for 5 minutes until completely uniform, and then the mixed glue liquid is injected into a preheated polytetrafluoroethylene mold. The mold is placed in a forced air oven and cured at 120°C for 1 hour, and then naturally cooled to room temperature. The mold is removed, and the cured sample and sheet are obtained for performance testing.

[0043] Performance test results: Total biobased content: 80%; Tensile shear strength: 33 MPa; T-peel strength: 40 N / mm; Heat distortion temperature: 172°C; Flame retardant level: V-0 level; Limiting oxygen index: 33%; Moisture and heat aging resistance (strength retention rate after 1000 hours): 90%.

[0044] Comparative Example 1 Bisphenol A type epoxy resin and polyamide curing agent are the most popular and classic petroleum-based epoxy systems. Aluminum hydroxide is one of the most commonly used and most economical halogen-free additive flame retardants in epoxy resins, but its addition amount usually needs to be very high (>50 phr) to achieve certain flame retardant effect, and it is prone to migration and can reduce mechanical properties.

[0045] Raw materials and proportions are by weight parts: Epoxy resin component: Bisphenol A type epoxy resin 80 parts, Nanya Plastic, model NPEL-128, epoxy value 0.51 eq / 100g; Curing agent component: polyamide curing agent 35 parts, Hexion, type Versamid 115, amine value 230-240 mgKOH / g.

[0046] Additive flame retardant: aluminum hydroxide 40 parts, particle size about 5 pm, industrial grade.

[0047] Preparation method: aluminum hydroxide was pre-dispersed in 80 parts of epoxy resin, then the curing agent was added, and stirred and mixed uniformly, and the curing conditions were: 80°C / 2 hours, 120°C / 1 hour.

[0048] Performance test: Solid content (ASTM D6866): <5%; Tensile shear strength (GB / T 7124): 18-22 MPa; Flame retardant grade (UL 94, 1.6mm): V-2 level; Limiting oxygen index (LOI): 26-28%; Flame retardant migration (60°C, 7 days): obvious white powder precipitated on the surface.

[0049] Strength retention rate after wet heat aging: 60-70%.

[0050] Comparative Example 2 Raw materials and proportions are by weight parts: Epoxy resin component: itaconic acid-based epoxy resin 50 parts, succinic acid-based epoxy resin 30 parts.

[0051] Curing agent component: tung oil maleic anhydride 35 parts, tung maleic anhydride, bio-based content >95%.

[0052] Preparation and curing: the raw materials of the epoxy resin component were added to a 500 mL three-necked flask equipped with a stirrer, temperature control device and vacuum interface, heated to 60°C, the stirring was started at a speed of 300 rpm, and the vacuum system was started at the same time to control the vacuum degree at -0.095 MPa. Under this condition, the temperature was kept and the stirring was kept for 45 minutes. The vacuum and heating were turned off, and the material was discharged to obtain a uniform and transparent component A, which was sealed and stored. The curing agent component was added to a 250 mL single-necked flask, which was placed in a 60°C water bath and mechanically stirred at a speed of 200 rpm for 30 minutes until the system became a uniform transparent liquid to obtain component B, which was sealed and stored. Before use, component A and component B were weighed in a beaker according to a mass ratio of 100:35, and stirred manually with a glass rod for 5 minutes until completely uniform. The mixed glue liquid was injected into a preheated polytetrafluoroethylene mold, which was placed in a forced air oven at 80°C for 2 hours, and then naturally cooled to room temperature, and demolded to obtain the cured sample and sheet, which were used for performance test.

[0053] Performance test: Total bio-based content: 80%.

[0054] Tensile shear strength: 25-28 MPa.

[0055] Flame retardant rating (UL 94, 1.6mm): no rating for severe combustion.

[0056] Limiting oxygen index (LOI): 19-21%.

[0057] Summary: Compared with Comparative Example 1, petroleum-based additive flame retardant, the environmental friendliness of Examples 1-3 of the present application has been greatly improved, the bio-based content has been increased from <5% to 75%-80%, the flame retardant migration problem has been solved, the flame retardant rating has been improved from temporary V-2 to permanent V-0, the comprehensive performance has been comprehensively improved, the mechanical strength has been increased by about 50%, and the aging resistance retention rate has been increased by more than 25% Compared with Comparative Example 2, it is proved that simply increasing the bio-based content cannot solve the flame retardant problem, highlighting the key role of the intrinsic flame retardant curing agent, and achieving a breakthrough from no rating to V-0 rating in flame retardant performance; The present application successfully solves the technical problem that high bio-based content and high flame retardancy cannot be achieved simultaneously for a long time by using a bio-based intrinsic flame retardant curing agent.

[0058] Finally, it should be noted that the disclosed embodiments of the present application only involve the structures involved in the disclosed embodiments, and other structures can be designed according to the usual design, and in the case of no conflict, the same embodiment and different embodiments of the present application can be combined with each other; Finally: The above only refers to the preferred embodiments of the present application, and does not limit the present application. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. An epoxy resin adhesive with high bio-based content and intrinsic flame retardancy, characterized in that: It is made by mixing and curing component A and component B in a mass ratio of 100:30 to 100:45; Component A is composed of the following components, and the sum of the weight parts of each component is 100 parts: 60 to 80 parts of bio-based epoxy resin; 5 to 12 parts of bio-based active diluent; 3 to 8 parts of bio-based toughening agent; Component B is composed of the following components, and the sum of the weight parts of each component is 100 parts: 20 to 35 parts of bio-based curing agent; 5 to 15 parts of bio-based flame retardant; 1 to 5 parts of bio-based accelerator; The bio-based flame retardant is phytic acid or phytate.

2. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based epoxy resin has an epoxy value of 0.45 eq / 100g to 0.55 eq / 100g.

3. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based epoxy resins include itaconic acid-based epoxy resins and succinic acid-based epoxy resins.

4. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The itaconic acid-based epoxy resin accounts for 40% to 60% of the total weight of the bio-based epoxy resin, and the succinic acid-based epoxy resin accounts for 20% to 40% of the total weight of the bio-based epoxy resin.

5. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based active diluent is eugenol glycidyl ether.

6. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based toughening agent is a cashew nut shell oil modified elastomer.

7. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based curing agent is cashew nut shell oil phenolic amine or rosin anhydride derivative.

8. The epoxy resin adhesive with high bio-based content and intrinsic flame retardancy according to claim 1, characterized in that: The bio-based accelerator is a lignin-derived phenolic accelerator.

9. A method for preparing the epoxy resin adhesive as described in claims 1-8, characterized in that: Includes the following steps: (1) Preparation of component A: Mix and stir the bio-based epoxy resin, bio-based reactive diluent and bio-based toughening agent at 50 to 70°C for 30 to 60 minutes; (2) Preparation of component B: Mix and stir the bio-based curing agent, bio-based flame retardant and bio-based accelerator at 40 to 60°C for 20 to 40 minutes; (3) When using, mix component A and component B at a mass ratio of 100:30 to 100:45 and cure at room temperature for 24 hours or at 80 to 120°C for 1 to 3 hours.

10. The method for using the epoxy resin adhesive according to claim 9, characterized in that: The mixing and stirring in step (1) is carried out under vacuum conditions, with a vacuum degree of -0.09MPa to -0.1MPa.

Citation Information

Patent Citations

  • Biological based degradable epoxy resin adhesive and preparation method thereof

    CN109021902A

  • Heat-conducting intrinsic flame-retardant lignin derivative-based epoxy resin composite material and preparation method thereof

    CN112961321A

  • Bio-based high-thermal-conductivity two-component epoxy structural adhesive and preparation method thereof

    CN118389108A

  • Anti-crack flame-retardant double-sided glass fiber adhesive tape and preparation method thereof

    CN119193032A

  • High-bonding-strength bio-based epoxy adhesive and preparation method thereof

    CN120775536A